HIV-1 and immunopathogenesis: innate immunity - Montaner, Luis (Henry Stewart Talks, 2009)
Viral life cycle, Acute infections, Immune response, Timeline to effectors, Stages of immunopathogenesis, Macrophages and HIV-1 infection, Monocyte apoptosis, Human DC subsets, Model of DC migration and maturation, MHC I antigen presentation, Proposed pathways of human DC development, C-type lectins, Nature killer cells, Natural killer cell recognition of target cells, Role of HLA and KIR alleles in rate of progression to AIDS, Measuring recovery following immune reconstitution and HIV-1 therapy, ART and innate reconstitution, Model of immune reconstitution timeline, Does the innate immune activation response determine HIV-1 disease?, Disease models: it's the activation